South Africa : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that economic growth in South Africa slowed in 2003 to 1.9 percent, from 3.6 percent in 2002, despite strong domestic demand. Fuelled by low interest rates, a more expansionary fiscal stance, and the wealth effects from strong commodity and property price increases, domestic expenditures rose strongly in 2003. Developments in 2004 point to a rebound in growth. Real GDP grew by 3.9 percent in the second quarter and a range of indicators, such as retail sales and consumer and business confidence measures, point to an acceleration in activity.